Social Anxiety in Adolescents and Young Adults: Translating Developmental Science Into Practice. 2011
DOI: 10.1037/12315-009
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety among lesbian, gay, bisexual, and transgender adolescents and young adults.

Abstract: Lesbian, gay, bisexual, and transgender (LGBT) adolescents and adults are notably underrepresented in the social anxiety literature. The lack of research on LGBT populations is striking in the face of evidence that social anxiety is higher among LGBT youth and adults than among heterosexuals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 84 publications
2
16
0
Order By: Relevance
“…This is considerably higher than past month prevalence rates reported for diverse HIV-infected samples but generally consistent with rates reported in samples of HIV-infected and HIV-uninfected gay and bisexual men. 2,40,41 Higher rates of social phobia among gay and bisexual men are expected, 42,43 and it has been suggested that gay men may have a developmental vulnerability for social anxiety. 44–46 Rates of screen in criteria for current panic disorder (9.5%) and generalized anxiety (7.8%) are also higher than those reported in diverse samples of HIV infected patients assessed with more conservative diagnostic measures.…”
Section: Discussionmentioning
confidence: 99%
“…This is considerably higher than past month prevalence rates reported for diverse HIV-infected samples but generally consistent with rates reported in samples of HIV-infected and HIV-uninfected gay and bisexual men. 2,40,41 Higher rates of social phobia among gay and bisexual men are expected, 42,43 and it has been suggested that gay men may have a developmental vulnerability for social anxiety. 44–46 Rates of screen in criteria for current panic disorder (9.5%) and generalized anxiety (7.8%) are also higher than those reported in diverse samples of HIV infected patients assessed with more conservative diagnostic measures.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive-behavioral approaches that address maladaptive cognitions appear promising in alleviating psychological distress related to previous victimization and anti-gay early life experiences (e.g., Hart, Tulloch, & O’Cleirigh, 2014 ; Satterfield & Crabb, 2010 ), and so may also be appropriate for syndemic-focused HIV prevention and sexual health promotion interventions for GBM. For example, anti-gay bullying and victimization in childhood may lead to high social anxiety, and social anxiety may lead to increased use of substances to manage sexual relationships (e.g., Roberts, Schwartz, & Hart, 2011 ; Terlecki & Buckner, 2015 ). Given that social anxiety is associated with high-risk sexual behavior (Hart & Heimberg, 2005 ; Hart, James, Purcell, & Farber, 2008 ), cognitive-behavioral interventions that treat social anxiety may also treat fears of rejection, substance use in sexual situations, and subsequent high-risk sexual behavior (Hart et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, TGNC youth have rates of social anxiety disorder that reportedly range from 9.5% to 31.4%. 2 , 5 , 23 Social anxiety disorder consists of anxiety specific to social situations where the possibility of being scrutinized by others exists and occurs in a variety of settings, including school, home, and social interactions. 3 Social anxiety disorder has a lifetime prevalence of 12.1% in the United States and can result in impaired social, academic, and work performance.…”
Section: Resultsmentioning
confidence: 99%
“… 25 This substantiates the assertion that transgender people experience higher rates of social anxiety disorder due to minority stress because while they face similar unfavorable life experiences as lesbian/gay/bisexual people, they also experience added distress because of their gender nonconformity and gender dysphoria. 23 Overall, social anxiety disorder in relevant populations such as sexual and gender minorities has been hypothesized to be related to minority stress. 5 , 23 , 25 We will next address evidence based treatments tailored to TGNC populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation